Die voedingswaarde van weimielies vir lammerooie in die Noord-Oos Vrystaat - Kriek, Daniel Johannes (University of the Free State, 1999)
The nutritive value of maize foggage cultivated on a low yield potential soil in the North Eastem Free State, with special reference to four yellow maize cultivars, was examined in a production study with Dohne Merino ewes and their lambs. Four yellow maize cultivars with the same growth season length, but differing in prolificacy, namely PAN 6364 (high prolific), SNK 2950 (semi high prolific), CRN 4512 (semi low prolific) and CRN 4502 (Iow prolific) were cultivated to be grazed as maize foggage by lactating ewes and their lambs. The experimental plot was fertilized with 35 kg N/ha, according to the planned grain yield of 2.5 t/ha. Normal tilling and production practices were applied during cultivation of the maize. The 120 Dohne Merino ewes used as experimental animals were randomly selected out of the local herd. The maize was grazed at a stocking rate of 15 ewes and lambs/ha during a 90-day grazing period. Dry material yield (DM-yield) and grain yield for cultivars were determined during the first month of the grazing period in order to quantify grazing material available to ewes and their lambs. A determination of residues not utilized by sheep during the grazing period was carried out after completion of the grazing period. The quality of grazing material available to ewes was examined in each of the three months of the grazing period, by use of feed samples collected by esophageal fistulated ewes. The dry material intake (DMI) and organic material intake (OMI) of twenty ewes, five per cultivar, were determined at the end of the first month of the grazing period, by use of the chromium oxide marker technique. The digestible organic material intake (DOMI) and crude protein intake (CPI) of ewes for the first month of the grazing period were calculated from the in vitro digestibility and chemical composition of feed samples collected by fistulated ewes. Ewes were weighed every two weeks and lambs every week from parturition till the end of the grazing period. The milk production of twenty ewes, five per cultivar, was determined during Week 1, 3, 5, 7, 9, 11, 13 and 15 of lactation by use of the oxytocin method. The ewes were introduced to maize foggage during Week 6 of lactation. The milk composition on percentage basis and production of milk components were investigated. Mid-rib wool samples were obtained just before parturition and again after completion of the grazing period, to ascertain the influence of quality of grazing material on wool fibre diameter of ewes. The estimated DM-yield for PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 4.996, 6.36, 5.126 and 4.381 Vha respectively. The estimated grain yield for PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 2.009, 2.782, 2.146 and 2.423 t/ha respectively. The percentage of available grazing material utilized by sheep and which disappeared due to weathering for PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 70.08,67.13,62.52 and 66.44 % respectively. Significant differences occurred in the chemical composition of feed samples collected by fistulated ewes during the first and third month of the grazing period. Significant differences occurred in ash content of cultivars during the first month of the grazing period, where ash content of PAN 6364 (20.12 %) and SNK 2950 (19.81 %) were significantly higher (P < 0.05) than that of CRN 4502 (5.39 %). Highly significant differences occurred in crude protein content of cultivars during the first month of the grazing period, where crude protein content of CRN 4512 (15.67 %) was significantly higher (P < 0.01) than that of CRN 4502 (8.53 %). Highly significant differences occurred in ADF-content of cultivars during the first month of the grazing period, where ADFcontent of CRN 4512 (23.54 %) was significantly higher (P < 0.01) than that of CRN 4502 (10.26 %). Significant differences occurred in ADF-content of cultivars during the third month of the grazing period, where ADF-content of CRN 4512 (39.04 %) was significantly higher (P < 0.05) than that of SNK 2950 (22.49 %). Highly significant differences occurred in DOM-content of cultivars during the first month of the grazing period, where DOM-content of PAN 6364 (76.48 %), SNK 2950 (75.73 %) and CRN 4502 (81.71 %) were significantly higher (P < 0.01) than that of CRN 4512 (66.6 %). The estimated DMI of ewes grazing PAN 6364, SNK 2950, CRN 4512 and CRN 4502 during the first month of the grazing period was 1680.45, 1385.54, 1323.61 and 2663.68 g/day respectively. The estimated DMI of ewes grazing PAN 6364, SNK 2950, CRN 4512 and DRN 4502 during the first month of the grazing period was 1342.34, 1111.06, 1113.95 and 2520.1 g/day respectively. The estimated DOMl of ewes grazing PAN 6364, SNK 2950, CRN 4512 and CRN 4502 during the first month of the grazing period was 1026.62, 841.41, 741.89 and 2059.17 g/day respectively. The estimated ME-intake of ewes grazing PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 15.9,13.0,11.5 and 31.9 MJ ME/day respectively, compared to the ME requirement of 14.2 MJ ME/day for ewes in late lactation. The estimated CPI of ewes grazing PAN 6364, SNK 2950, CRN 4512 and CRN 4502 during the first month of the grazing period was 156.11, 138.99, 174.56 and 214.96 g/day respectively, compared to the total crude protein requirement of 175 g/day for ewes in late lactation. The difference in crude protein content of selected grazing material of different cultivars, can be exempted as the most important factor which influenced the mass gain of ewes and lambs and the milk production response of ewes. No significant differences occurred in the average mass of lambs grazing different cultivars during the first 49 days of the grazing period. Significant differences occurred in the average mass of lambs at day 61, where the average mass of lambs grazing CRN 4512 (26.36 kg) was significantly higher (P < 0.05) than that of lambs grazing CRN 4502 (22.46 kg). Significant differences occurred in the average mass of lambs at day 72 and 82, where the average mass of lambs grazing CRN 4512 (28.69 and 29.81 kg) and SNK 2950 (27.27 and 30.37 kg) were significantly higher (P < 0.05) than that of lambs grazing CRN 4502 (23.63 and 25.56 kg). Significant differences occurred in the average mass of lambs at day 95, where the average mass of lambs grazing SNK 2950 (29.32 kg) was significantly higher (P < 0.05) than that of lambs grazing CRN 4502 (25.05 kg). The average daily gain (ADG) of lambs on day 82 of the grazing period for PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 187.32, 211.59, 205.24 and 160.37 g/day respectively. No significant differences (P > 0.05) occurred in the average mass of ewes grazing different cultivars during the grazing period. The ADG of ewes on day 72 of the grazing period for PAN 6364, SNK 2950, CRN 4512 and CRN 4502 was 106.53, 110.69, 131.39 and 96.39 g/day respectively. Milk production of ewes up to Week 13 of lactation did not differ significantly (P > 0.05) amongst cultivars. Significant differences in milk production of ewes only occurred during Week 15 of lactation, where milk production of ewes grazing CRN 4512 (537.49 g/day) was significantly higher (P < 0.05) than that of ewes grazing CRN 4502 (219.97 g/day). The milk production of ewes grazing CRN 4512 was characterized by an immediate increase after introduction to maize foggage, where after it declined gradually, but increased again during Week 15. The milk production of ewes grazing PAN 6364 and SNK 2950 maintained a constant level after introduction to maize foggage, where after it declined gradually. The milk production of ewes grazing CRN 4502 was characterized by a slight increase after introduction to maize foggage, where after it declined rapidly. Milk composition and production of milk components, accept for a few instances, did not differ significantly (P > 0.05) amongst cultivars. Significant differences in milk fat content occurred during Week 9 of lactation, where milk fat content on PAN 6364 (9.42 %) was significantly higher (P < 0.05) than that on CRN 4502 (6.2 %). Significant differences in milk fat production occurred during Week 7 and 9 of lactation, where milk fat production on PAN 6364 (64.51 and 57.51 g/day) were significantly higher (P < 0.05) than that on CRN 4502 (39.39 and 22.35 g/day). No significant differences (P > 0.05) in milk protein content occurred amongst cultivars. Significant differences in milk protein production occurred during Week 15 of lactation, where milk protein production on CRN 4512 (40.71 g/day) was significantly higher (P < 0.05) than that on CRN 4502 (16.7 g/day). No significant differences (P > 0.05) in lactose content of milk occurred amongst cultivars. Significant differences in lactose production occurred during Week 15 of lactation, where lactose production on CRN 4512 (29.5 g/day) was significantly higher (P < 0.05) than that on CRN 4502 (11.13 g/day). No significant differences (P > 0.05) in total solids content of milk occurred amongst cultivars. Significant differences in total solids production occurred during Week 15 of lactation, where total solids production on CRN 4512 (110.47 g/day) was significantly higher (P < 0.05) than that on CRN 4502 (49.99 g/day). No significant differences (P > 0.05) occurred in wool fibre diameter of ewes grazing different cultivars after completion of the grazing period. Lambs grazing SNK 2950 and CRN 4512 attained the highest mass gain during the grazing period of 17.35 and 16.83 kg/lamb and consequently attained the highest gross margin of R 447.52/ha and R 404.62/ha respectively. Lambs grazing PAN 6364 and CRN 4502 attained a lower mass gain during the grazing period of 15.36 and 13.15 kg/lamb and consequently attained a gross margin of R 283.34/ha and R 101.02/ha respectively. The utilization of maize foggage by ewes and their lambs during the critical winter months in the North Eastern Free State, can play a significant role in bridging the gap in fodder flow usually experienced at this time of year. Maize foggage produces fodder of sufficient quantity and quality to ewes and their lambs, which can contribute to excellent growth results, an increase in milk production of ewes and a decrease in the occurrence of tender fleeces. The utilization of maize foggage by ewes and their lambs is economically profitable and only in instances of high grain prices prevailing, will a higher gross margin per hectare be realized.

Die voedingswaarde van weimielies op 'n lae opbrengspotensiaal grond in die Noord-Oos Vrystaat, is aan die hand van vier geelmieliekultivars in 'n produksiestudie met Dohnemerino lammerooie ondersoek. Vier geelmieliekultivars van dieselfde groeiseisoenlengte, maar wat in hul meerkoppigheid verskil, naamlik PAN 6364 (sterk meerkoppig), SNK 2950 (medium-sterk meerkoppig), CRN 4512 (medium-swak meerkoppig) en CRN 4502 (swak meerkoppig) is aangeplant om as weimielies deur lammerooie benut te word. Bemesting van die proefarea is na aanleiding van die beplanningsopbrengs vir die studie van 2.5 Uha op 35 kg Nlha vasgestel. Normale bewerkingsen produksiepraktyke is tydens die verbouing van die mielies gevolg. Die 120 Dohnemerino ooie wat vir die beweiding van die mielies gebruik is, is volledig ewekansig uit die plaaslike kudde geselekteer. Die mielies is teen 'n veebelading van 15 lammerooie/ha oor 'n 90 dae periode bewei. Die hoeveelheid weiding tot die lammerooie se beskikking is gedurende die eerste maand van die weiperiode deur middel van 'n droëmateriaalopbrengsbepaling (DM-opbrengs) en graanopbrengsbepaling vir elke kultivar gekwantifiseer. 'n Bepaling van die onbenutte reste op elke kultivar is na afloop van die weiperiode uitgevoer. Die kwaliteit weiding wat deur elke kultivar verskaf is, is in elk van die drie maande van die weiperiode met behulp van fistelmonsters, wat deur slukdermgefistuleerde ooie versamel is, bepaal. Die DM-voerinname (DMI) en OMvoerinname (OMI) van twintig ooie, vyf per behandeling, is aan die einde van die eerste maand van die weiperiode deur middel van die chroomoksiedmerkermetode bepaal. Die verteerbare organiese materiaalinname (VDMI) en ruproteïeninname (RPI) van ooie vir die eerste maand van die weiperiode is vanaf die in vitro verteerbaarheid en chemiese samestelling van fistelmonsters bereken. Die ooie is tweeweekliks en lammers weekliks vanaf lamtyd tot aan die einde van die weiperiode geweeg. Die melkproduksie van twintig ooie, vyf per behandeling, is in Week 1, 3, 5, 7, 9, 11, 13 en 15 van laktasie met behulp van die oksitosienmetode bepaal. Die ooie is gedurende Week 6 van laktasie op die weimielies geplaas. Die persentasie melksamestelling en die produksie van melkbestanddele is ondersoek. 'n Midribwolmonster is net voor lamtyd en weer aan die einde van die weiperiode op al die ooie skoongeskeer, om die invloed van mieliebeweiding op die veseldikte te ondersoek. Die beraamde DM-opbrengs van PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 4.996, 6.36, 5.126 en 4.381 t/ha. Die beraamde graanopbrengs van PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 2.009,2.782,2.146 en 2.423 t/ha. Die persentasie van die beskikbare weiding wat deur skape benut is en deur verwering verlore gegaan het vir PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 70.08,67.13, 62.52 en 66.44 %. Betekenisvolle verskille in die chemiese samestelling van fistelmonsters tussen kultivars, het gedurende die eerste en derde maand van die weiperiode voorgekom. Betekenisvolle verskille in die asinhoud tussen kultivars het gedurende die eerste maand van die weiperiode voorgekom, met die asinhoud van PAN 6364 (20.12 %) en SNK 2950 (19.81 %) wat betekenisvol hoër (P < 0.05) as die van CRN 4502 (5.39 %) was. Hoogs betekenisvolle verskille in die ruproteïeninhoud tussen kultivars het gedurende die eerste maand van die weiperiode voorgekom, met die ruproteïeninhoud van CRN 4512 (15.67 %) wat betekenisvol hoër (P < 0.01) as die van CRN 4502 (8.53 %) was. Hoogs betekenisvolle verskille in die ADF-inhoud tussen kultivars het gedurende die eerste maand van die weiperiode voorgekom, met die ADF-inhoud van CRN 4512 (23.54 %) wat betekenisvol hoër (P < 0.01) as die van CRN 4502 (10.26 %) was. Betekenisvolle verskille in die ADF-inhoud tussen kultivars het gedurende die derde maand van die weiperiode voorgekom, met die ADF-inhoud van CRN 4512 (39.04 %) wat betekenisvol hoër (P < 0.05) as die van SNK 2950 (22.49 %) was. Hoogs betekenisvolle verskille in die persentasie VaM tussen kultivars het gedurende die eerste maand van die weiperiode voorgekom, met die persentasie VOM van PAN 6364 (76.48 %), SNK 2950 (75.73 %) en CRN 4502 (81.71 %) wat betekenisvol hoër (P < 0.01) as die van CRN 4512 (66.6 %) was. Die beraamde DMI van ooie vir die eerste maand van die weiperiode op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 1680.45, 1385.54, 1323.61 en 2663.68 g/dag. Die beraamde aMI van ooie vir die eerste maand van die weiperiode op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 1342.34, 1111.06, 1113.95 en 2520.1 g/dag. Die beraamde VOMI van ooie vir die eerste maand van die weiperiode op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 1026.62, 841.41, 741.89 en 2059.17 g/dag. Na beraming het ooie op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 onderskeidelik 15.9, 13.0, 11.5 en 31.9 MJ ME/dag, teenoor die ME-benodigdheid van 14.2 MJ ME/dag vir laat laktasie ingeneem. Die beraamde RPI van ooie vir die eerste maand van die weiperiode op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 156.11,138.99,174.56 en 214.96 g/dag, teenoor die benodigdheid vir laat laktasie van 175 g TRP/dag. Die verskil in die ruproteïeninhoud van die geselekteerde weidingsmateriaal tussen kultivars, kan as die belangrikste faktor wat die massatoename van ooie en lammers en melkproduksierespons van ooie beïnvloed het, uitgesonder word. Geen betekenisvolle verskille (P > 0.05) in die gemiddelde massa van lammers tussen kultivars het tot en met dag 49 voorgekom nie. Vanaf dag 61 het betekenisvolle verskille voorgekom, met die gemiddelde massa van lammers op CRN 4512 (26.36 kg) wat betekenisvol hoër (P < 0.05) as lammers op CRN 4502 (22.46 kg) was. Op dae 72 en 82 was die gemiddelde massa van lammers op CRN 4512 (28.69 en 29.81 kg) en SNK 2950 (27.27 en 30.37 kg) betekenisvol hoër (P < 0.05) as lammers op CRN 4502 (23.63 en 25.56 kg). Op dag 95 was die gemiddelde massa van lammers op SNK 2950 (29.32 kg) betekenisvol hoër (P < 0.05) as lammers op CRN 4502 (25.05 kg). Die gemiddelde daaglikse toename (GDT) van lammers op dag 82 van die weiperiode vir PAN 6364, SNK 2950, CRN 4512 en CRN 4502 was onderskeidelik 187.32,211.59,205.24 en 160.37 g/dag. Geen betekenisvolle verskille (P > 0.05) in gemiddelde massa van ooie tussen kultivars het oor die weiperiode voorgekom nie. Die GDT van ooie op PAN 6364, SNK 2950, CRN 4512 en CRN 4502 op dag 72 was onderskeidelik 106.53,110.69,131.39 en 96.39 g/dag. Melkproduksie van ooie het tot en met Week 13 van laktasie, nie-betekenisvol (P > 0.05) tussen kultivars verskil. Betekenisvolle verskille in die melkproduksie van ooie tussen kultivars het in Week 15 van laktasie voorgekom, waar die melkproduksie van ooie op CRN 4512 (537.49 g/dag) betekenisvol hoër (P < 0.05) as die van ooie op CRN 4502 (219.97 g/dag) was. Ooie op CRN 4512 se melkproduksie het 'n onmiddellike styging na aanvang van mieliebeweiding na Week 7 van laktasie getoon, waarna dit geleidelik gedaal en by Week 15 weer 'n styging getoon het. Ooie op PAN 6364 en SNK 2950 se melkproduksie het aanvanklik konstant gebly, waarna dit geleidelik gedaal het. Ooie op CRN 4502 se melkproduksie het effens gestyg, maar het daarna 'n volgehoue daling getoon. Melksamestelling en die produksie van melkbestanddele het met enkele uitsonderings, niebetekenisvol (P > 0.05) tussen kultivars verskil. Betekenisvolle verskille in bottervetinhoud het in Week 9 van laktasie voorgekom, waar die bottervetinhoud van melk op PAN 6364 (9.42 %) betekenisvol hoër (P < 0.05) as die van melk op CRN 4502 (6.2 %) was. Betekenisvolle verskille in bottervetproduksie het gedurende Week 7 en 9 van laktasie voorgekom, waar die bottervetproduksie van ooie op PAN 6364 (64.51 en 57.51 g/dag) betekenisvol hoër (P < 0.05) as die van ooie op CRN 4502 (39.39 en 22.35 g/dag) was. Geen betekenisvolle verskille (P > 0.05) in melkproteïeninhoud tussen kultivars het voorgekom nie. Betekenisvolle verskille in melkproteïenproduksie van ooie tussen kultivars het in Week 15 van laktasie voorgekom, waar die melkproteïenproduksie van ooie op CRN 4512 (40.71 g/dag) betekenisvol hoër (P < 0.05) as die van ooie op CRN 4502 (16.7 g/dag) was. Geen betekenisvolle verskille (P > 0.05) in laktoseinhoud van melk tussen kultivars het voorgekom nie. Betekenisvolle verskille in laktoseproduksie van ooie tussen kultivars het in Week 15 van laktasie voorgekom, waar die laktoseproduksie van ooie op CRN 4512 (29.5 g/dag) betekenisvol hoër (P < 0.05) as die van ooie op eRN 4502 (11.13 g/dag) was. Geen betekenisvolle verskille (P > 0.05) in totale vastestofinhoud van melk tussen kultivars het voorgekom nie. Betekenisvolle verskille in totale vastestofproduksie van ooie tussen kultivars het in Week 15 van laktasie voorgekom, waar die totale vastestofproduksie van ooie op CRN 4512 (110.47 g/dag) betekenisvol hoër (P < 0.05) as die van ooie op CRN 4502 (49.99 g/dag) was. Geen betekenisvolle verskille (P > 0.05) in wolveseldikte het by ooie op verskillende kultivars na afloop van die weiperiode voorgekom nie. Lammers op SNK 2950 en CRN 4512 het die hoogste massatoename van onderskeidelik 17.35 en 16.83 kg/lam, met gevolglik die hoogste bruto marge van onderskeidelik R 447.52/ha en R 404.62/ha oor die weiperiode behaal. Lammers op PAN 6364 en CRN 4502 het 'n laer massatoename van onderskeidelik 15.36 en 13.15 kg/lam, met gevolglik 'n laer bruto marge van onderskeidelik R 283.34/ha en R 101.02/ha oor die weiperiode behaal. Die benutting van weimielies deur lammerooie gedurende die kritiese wintermaande in die Noord- Oos Vrystaat, kan 'n belangrike bydrae lewer om die gaping in die voervloeiprogram wat normaalweg gedurende hierdie tydperk ondervind word, te oorbrug. Weimielies lewer hoë kwaliteit en kwantiteit weiding aan lammerooie, wat uitstekende groeiresultate, 'n verhoging in die melkproduksie van die ooi en 'n afname in die voorkoms van breekwol teweeg kan bring. Die produksiestelsel is ekonomies winsgewend en slegs in die geval van hoë mieliepryse kan 'n hoër bruto marge per hektaar behaal word.
Dissertation (M.Sc.Agric. (Animal Science))--University of the Free State, 1999
Keywords: Lambs -- Feeding and feeds; Corn as feed